Which students can reach higher proficiency in speaking and reading those taking classes a blended learning a approach versus those taking classes a face- to face approach in advanced intensive english I at Foreign Language Department of the University of El Salvador during year 2014 - Molina Cruz, Wilson Jonathan; Córdova Carbajal, Walter Francisco; Aguilar de Orellana, Elsy Noemy; Gamero Ortiz, Ricardo; Ayala, Edgar Nicolás (San Salvador, El Salvador. Universidad de El Salvador, 2015)
This research is very significant as it will help to improve not only the Intensive Advanced English I courses, but also, its findings could be applied to other courses where a blended approach is applied. We aim to test whether or not the reading and speaking skills studied in the Intensive English Advance I courses are put into practice.
Incluye anexos.
Tesis para obtener el grado de --(Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2015
Bibliografía: 172
Keywords: Inglés -- Enseñanza